The Role of Digital Literacy and Entrepreneurial Knowledge on Technopreneurship Intention - Nugroho, Prasetyo Adi; Nurjanah, Siti; Pitaloka, Endang; Tambun, Sihar (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2025)
The purpose of this research is to prove whether there is an influence of digital literacy and entrepreneurship knowledge on technopreneurship intention moderated by ICT self-efficacy. This research can provide a much better understanding of how an individual can develop the intention to become a technopreneur, along with their digital literacy, entrepreneurship knowledge, and ICT self-efficacy. A survey was conducted with 150 entrepreneurs as respondents. The collected data were analyzed using structural equation modeling (SEM) with SmartPLS, a variance-based structural equation modeling approach.. The results of this study indicate that Digital Literacy has a positive effect on Technopreneurship Intention, Entrepreneurship Knowledge has no effect on Technopreneurship Intention, ICT self efficacy has a positive effect on Technopreneurship Intention, moderation of ICT Self Efficacy fails to strengthen the positive effect of digital literacy on technopreneurship intention, moderation of ICT Self Efficacy fails to strengthen the positive effect of entrepreneurship knowledge on technopreneurship intention. These results can provide an overview of what individuals must do or need to achieve their desire to become a technopreneur. If someone has good digital skills, they will be more confident in finding and utilizing technology business opportunities, it is very important to deeply understand the potential of technology entrepreneurship.